Development and Validation of LC-APCI-MS Method for the Estimation of Ellagic acid in Fresh and Processed Fruit Products - Krishna Veni N., Meyyanathan S N., Gowramma B., Babu B and Elango K (Journal of Applied Pharmaceutical Science, 2013)
A rapid and simple LC/MS method has been developed for the quantification of ellagic acid in fresh and processed fruits. The interface used was Atmospheric Pressure Chemical Ionization technique. Analysis was performed using a Princeton SPHER C18 column (100 X 4.6 mm) by isocratic elution with 10 mM ammonium acetate: Acetonitrile (20:80) at a flow rate of 1.0 ml/min. The calibration plot was linear over the range studied (Ellagic acid: 80 – 1300 ng/ml) with a correlation of 0.999. The (M-H) peak of ellagic acid was identified at m/z of 302 in selective ion monitoring mode. Two fresh fruits and two processed fruit products were subjected to analysis by the developed method. The samples were found to contain ellagic acid in the range of 18.20-97.80 µg/10 gm of the products consumed. The method was also validated for the precision and recovery. Thus the method is suitable for routine analysis of ellagic acid in fresh and processed fruits.
Keywords: Ellagic acid, LC/MS, fresh and processed fruits, Val